Local delivery of minocycline from metal ion-assisted self-assembled complexes promotes neuroprotection and functional recovery after spinal cord injury. (January 2017) - Wang, Zhicheng; Nong, Jia; Shultz, Robert B.; Zhang, Zhiling; Kim, Taegyo; Tom, Veronica J.; Ponnappan, Ravi K.; Zhong, Yinghui
Abstract: Many mechanisms contribute to the secondary injury cascades following traumatic spinal cord injury (SCI). However, most current treatment strategies only target one or a few elements in the injury cascades, and have been largely unsuccessful in clinical trials. Minocycline hydrochloride (MH) is a clinically available antibiotic and anti-inflammatory drug that has been shown to target a broad range of secondary injury mechanisms via its anti-inflammatory, anti-oxidant, and anti-apoptotic properties. However, MH is only neuroprotective at high concentrations. The inability to translate the high doses of MH used in experimental animals to tolerable doses in human patients limits its clinical efficacy. In addition, the duration of MH treatment is limited because long-term systemic administration of high doses of MH has been shown to cause liver toxicity and even death. We have developed a drug delivery system in the form of hydrogel loaded with polysaccharide-MH complexes self-assembled by metal ions for controlled release of MH. This drug delivery system can be injected into the intrathecal space for local delivery of MH with sufficient dose and duration, without causing any additional tissue damage. We show that local delivery of MH at a dose that is lower than the standard human dose (3 mg/kg) was more effective in reducing secondary injury and promoting locomotor functional recovery than systemic injection of MH with the highest dose and duration reported in experimental animal SCI (90–135 mg/kg). Graphical abstract: